Natural gas supply: No need for another Baltic Sea pipeline - Anne Neumann; Leonard Göke; Franziska Holz; Claudia Kemfert; Christian von Hirschhausen (DIW Weekly Report, 2018)
The construction of a second Baltic Sea natural gas pipeline from Russia to Germany (Nord Stream 2) is very controversial for political, energy economic, and ecological reasons. The project owner and some European energy companies argue that it is a profitable, private-sector investment project that is necessary to secure natural gas supplies for Germany and Europe. However, DIW Berlin analyses show that the planned pipeline project Nord Stream 2 is not necessary to secure natural gas supplies for Germany and Europe. The energy consumption forecasts on which the project is based, especially the EU Reference Scenario, significantly overestimate natural gas demand in Germany and Europe. On the supply side, there will be no supply gap if Nord Stream 2 is not built. Different profitability studies suggest that high losses up to the billions can be expected from the project. It is also unclear to what extent Nord Stream 2 would lead to higher prices for natural gas customers in Germany.
Keywords: L51; L94; Q48; 330; natural gas; pipeline; Nord Stream 2; Russia; Germany; Europe